Exhaust gas treatment catalyst, and production method thereof
Patent Information
- Application Number
- JP2022043474
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-18
- Publication Date
- 2025-03-05
AI Technical Summary
Existing exhaust gas treatment catalysts face challenges in maintaining high nitrogen oxide removal efficiency in the presence of sulfur oxides, and there is a need for catalysts that are durable and active even at lower operating temperatures to reduce dioxin generation.
A composite oxide containing vanadium and molybdenum, adhered to the surface of titanium oxide, with a specific peak area ratio in NMR spectra, and incorporating a silane coupling agent and latex, is used to create a catalyst with high nitrogen oxide removal efficiency and resistance to sulfur oxides.
The catalyst maintains high nitrogen oxide removal efficiency and selective reduction activity, even in the presence of sulfur oxides, and operates effectively at temperatures between 150°C and 400°C, particularly showing good activity between 170°C and 270°C.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention is SO X This invention relates to an exhaust gas treatment catalyst that exhibits high nitrogen oxide removal efficiency even in the presence of nitrogen oxides, and to a method for producing the same. [Background technology]
[0002] Conventionally, nitrogen oxides (NOx) in exhaust gas X As an exhaust gas treatment catalyst that selectively reduces and removes ) with a reducing agent such as ammonia, a honeycomb-shaped catalyst molded product in which active components such as tungsten oxide and vanadium oxide are supported on a titanium oxide support is used industrially (Patent Documents 1 and 2), and the valence of V and NO X Studies have also been conducted on the relationship with the conversion rate (Non-patent documents 1-5). In recent years, it has also been used as a catalyst to remove nitrogen oxides from exhaust gases of boilers, waste incinerators, etc., and operation at temperatures below approximately 200°C is desired from the perspective of suppressing the generation of dioxins. As an exhaust gas treatment catalyst that solves this problem, Patent Document 1 describes research on a denitrification catalyst using titanium oxide with a high specific surface area as a support. Specifically, it has been reported that by treating it with a silane coupling agent, a high specific surface area can be maintained, and a denitrification catalyst with high activity and excellent heat resistance can be obtained. Patent Documents 2 and 3 also propose exhaust gas treatment catalysts, etc., and SO X There is a growing demand for exhaust gas treatment catalysts that remain highly active even in the presence of certain substances. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2003-080067 [Patent Document 2] Japanese Patent Application Publication No. 11-309376 [Patent Document 3] Japanese Patent Application Publication No. 10-151343 [Non-patent literature]
[0004] [Non-Patent Document 1] Geert Silversmit et al., Determination of the V2p XPS binding energies for different vanadium oxidation states(V5+toV6+), J. Electron Spectroscopy and Related Phenomena, 2004, 135(2-3), 167-175. [Non-Patent Document 2] Geert Silversmit et al., An XPS study on the surface reduction of V2O5(001) induced by Ar+ion bombardment, Surface Science, 2006, 600(17), 3512-3517. [Non-Patent Document 3] Xuteng Zhao et al., A relationship between the V4+ / V5+ratio and the surface dispersion, surface acidity, and redox performance of V2O5-WO3 / TiO2 SCR catalysts, RSC Advances, 2018, 8, 31081-31093. [Non-Patent Document 4] Jiaoyan Zhou et al., Manipulating Behaviors from Heavy Tungsten Doping on interband Electronic Transition and Orbital Structure Variation of Vanadium Dioxide Films, ACS Appl. Mater. Interfaces, 2018, 10(36), 30548-30557, [Non-Patent Document 5] Jihene Arfaoui et al., A new V2O5 -MoO3 -TiO2 -SO4 2- nanostructured aerogel catalyst for diesel DeNO x technology, New Journal of Chemistry, Royal Society of Chemistry, 2020, 44 (37), pp.16119-16134 [Non - Patent Document 6] Asahi Glass Research Report, 2016, 66, Structural Analysis of Silicon - containing Materials by 29Si - NMR Method [Summary of the Invention] [Problems to be Solved by the Invention]
[0005] The present invention provides an exhaust gas treatment catalyst with high nitrogen oxide removal efficiency even in the presence of SO X and having SO X resistance, and a method for producing the same. [Means for Solving the Problems]
[0006] The inventor has intensively studied to solve the above problems and completed the present invention. The present invention is as follows in [1] to [4]. [1] A composite oxide containing vanadium and molybdenum, which is composed of a mixed valence compound of vanadium and molybdenum containing trivalent, tetravalent and pentavalent vanadium and hexavalent molybdenum, is fixed on the surface of a titanium oxide, and the peaks obtained by performing Si - NMR are separated into Q1 to Q4, and the exhaust gas treatment catalyst having a peak area ratio of (Q1 + Q2) / (Q3 + Q4 ) of 4 / 5 or more. [2] The exhaust gas treatment catalyst according to [1] above, wherein the catalyst further contains a silane coupling agent and latex. [3] The raw material of the titanium oxide is a powder having a specific surface area of 250 - 500 m 2 / g, and the exhaust gas treatment catalyst according to [1] or [2] above. [4] 1) A step of kneading water, sulfuric acid, a vanadium raw material, a molybdenum raw material, and a complexing agent to prepare a mother liquor. 2) A step of kneading a titanium oxide powder and the mother liquor to prepare a kneaded product, kneading a precipitating agent into the kneaded product, and obtaining a kneaded product for molding containing a coprecipitate of vanadium and molybdenum fixed on the surface of the titanium oxide powder, further containing a silane coupling agent and latex. 3) A step of molding the kneaded product for molding to obtain a molded body. 4) A step of firing the molded body to obtain an exhaust gas treatment catalyst in which a composite oxide of vanadium and molybdenum is fixed on the surface of the titanium oxide powder. A method for manufacturing an exhaust gas treatment catalyst including the above steps.
Effects of the Invention
[0007] The exhaust gas treatment catalyst of the present invention is an exhaust gas treatment catalyst that maintains a high nitrogen oxide removal efficiency even in the presence of SO X Also, since the selective reduction activity of NO X is high, not only in the high temperature range but also in the low temperature range of about 200 ° C or lower, NO X can be efficiently removed and SO X resistance can be exhibited.
Brief Description of the Drawings
[0008] [Figure 1] It is the NMR spectrum of the exhaust gas treatment catalyst obtained in Example 1. [Figure 2] It is a scanning electron microscope (SEM) image of the exhaust gas treatment catalyst obtained in Example 1. [Figure 3] It is a scanning electron microscope (SEM) image of the exhaust gas treatment catalyst obtained in Comparative Example [[ID=比较例2で得られた排ガス処理触媒の走査型電子顕微鏡(SEM)画像である。
Modes for Carrying Out the Invention
[0011] The vanadium and molybdenum composite oxide is preferably composed of a mixed-valence compound containing trivalent, tetravalent, and pentavalent vanadium and hexavalent molybdenum. By analyzing the surface of the exhaust gas treatment catalyst of this invention by X-ray photoelectron spectroscopy (XPS) as described below, it can be confirmed that the composite oxide contains vanadium and molybdenum of these valencies.
[0012] The vanadium-molybdenum composite oxide referred to here is bonded to the surface of the titanium oxide. This is different from a composite oxide in which vanadium, molybdenum, and titanium are mixed within the same crystal structure; rather, the vanadium-molybdenum composite oxide is bonded to the surface of the titanium oxide via oxygen. This clearly distinguishes the composite oxide phase from the titanium oxide phase.
[0013] The composite oxide contains vanadium in an amount of V2O5 equivalent, preferably 3.0 to 10.0% by mass, and molybdenum in an amount of MoO3 equivalent, preferably 3.0 to 20.0% by mass, more preferably 3.0 to 8.0% by mass.
[0014] The exhaust gas treatment catalyst of the present invention is formed by fixing vanadium and molybdenum on titanium in an oxide state of suitable active species. Furthermore, when the NMR spectrum obtained by NMR measurement of the exhaust gas treatment catalyst of the present invention is separated by the method described in the examples below and the peak areas assigned to Q1 to Q4 are determined, the peak area ratio of (Q1+Q2) / (Q3+Q4) is 4.5 or more.
[0015] The titanium oxide is preferably titanium dioxide.
[0016] The exhaust gas treatment catalyst of the present invention has a specific surface area of 250 to 500 m². 2 It is preferable that the product is manufactured using a titanium oxide raw material powder in a quantity of / g.
[0017] Conventionally, exhaust gas treatment catalysts with a large specific surface area have been used to remove NO X It is known to have good selective reduction activity. In contrast, the exhaust gas treatment catalyst of the present invention has good NO reduction activity even with a small specific surface area. X It exhibits selective reduction activity. Specifically, at 100m 2 Even if it is less than / g, 50m 2 / g or more 95m 2 Even in the range of less than / g, good NO x It exhibits selective reducing activity.
[0018] The exhaust gas treatment catalyst of the present invention may contain components other than the vanadium and molybdenum composite oxide. For example, components other than vanadium and molybdenum may include metal components such as tungsten, chromium, manganese, iron, nickel, copper, silver, gold, palladium, yttrium, cerium, neodymium, indium, iridium, and antimony. These act as co-catalysts and affect the catalytic performance, and their content (in terms of metal oxides) is preferably 3% by mass or less.
[0019] The exhaust gas treatment catalyst of the present invention preferably contains sulfur. The sulfur content (SO4 equivalent) is preferably in the range of 0.1% to 5% by mass, more preferably in the range of 0.5% to 4% by mass, and particularly preferably in the range of 0.5% to 3% by mass. The sulfur contained in the exhaust gas treatment catalyst of the present invention affects the band structure of vanadium, and NO X It has a positive effect on selective reduction activity.
[0020] In addition to these components, additives may be added during the molding process. Examples of additives include reinforcing agents and plasticizers. The catalyst may also contain inorganic components such as glass fibers, silica, and alumina as additives. These components enhance the moldability of the exhaust gas treatment catalyst and maintain its strength. Furthermore, it is preferable to add latex as an additive, and more preferably to add acrylate-based latex. By adding this additive and glass fiber, vanadium and molybdenum can be fixed to titanium in a preferred oxide state in a highly dispersed state. This contributes to improving catalytic performance. When reinforcing materials and plasticizers are used as additives, the total content of the reinforcing materials and plasticizers relative to the total amount of the exhaust gas treatment catalyst of the present invention is preferably 5 to 30% by mass. More preferably, it is 5 to 15% by mass. When latex, preferably acrylate latex (for example, with a concentration of 45%), is used as an additive, the content of latex (preferably acrylate latex) relative to the total amount of the exhaust gas treatment catalyst of the present invention is preferably 0.02 to 5.0% by mass. More preferably, it is 0.05 to 1.0% by mass.
[0021] Furthermore, a silane coupling agent may be added as an additive.
[0022] The exhaust gas treatment catalyst of the present invention preferably contains a silane coupling agent having an ethylene skeleton (C=C double bond). The content of the silane coupling agent relative to the total amount of the exhaust gas treatment catalyst of the present invention is preferably 0.5% by mass or more and 10.0% by mass or less.
[0023] Preferably, the exhaust gas treatment catalyst of the present invention further contains a silane coupling agent and latex. When the exhaust gas treatment catalyst of the present invention contains a silane coupling agent, the content of the silane coupling agent relative to the total amount of raw materials used in the production of the exhaust gas treatment catalyst of the present invention is preferably 0.5 to 10.0% by mass. When the exhaust gas treatment catalyst of the present invention contains latex, the latex content relative to the total amount of raw materials used in the production of the exhaust gas treatment catalyst of the present invention is preferably 0.02 to 5.0% by mass. More preferably, it is 0.05 to 1.0% by mass.
[0024] Furthermore, when the NMR spectrum obtained by the NMR measurement method described below is separated by the method described in the examples below and the respective peak areas assigned to Q1 to Q4 are determined, the peak area ratio of (Q1+Q2) / (Q3+Q4) is 4.5 or greater.
[0025] The shape of the exhaust gas treatment catalyst of the present invention may be a conventionally known shape such as a pellet or a honeycomb, and a honeycomb is preferred. To explain using a honeycomb with a square cross-sectional shape perpendicular to the longitudinal direction (through-direction) of the through-hole as an example, it is preferable that the outer diameter of the honeycomb (the length of one side of its cross-section) be in the range of 30 mm to 300 mm, and more preferably in the range of 50 mm to 200 mm. The length of the honeycomb (length in the longitudinal direction of the through-hole) is preferably in the range of 100 mm to 3000 mm, and more preferably in the range of 300 mm to 1500 mm. The through-holes in the honeycomb (hereinafter sometimes referred to as cell pitch) are preferably in the range of 1 mm to 15 mm in terms of the equivalent diameter of an equal-area circle in the cross-section, and more preferably in the range of 2 mm to 10 mm. The thickness of the honeycomb partitions is preferably in the range of 0.1 mm to 2 mm, and more preferably in the range of 0.1 mm to 1.5 mm. The opening ratio of the honeycomb is preferably in the range of 60% to 85%, and more preferably in the range of 70% to 85%. The opening ratio is defined as the ratio of the area of the through-holes through which the reaction gas flows, where there is no catalyst, to the cross-sectional area of the honeycomb catalyst in the direction of reaction gas flow velocity, minus the area occupied by the catalyst area. When the honeycomb shape is within this range, the strength of the honeycomb structure is maintained while the NO per unit volume is reduced. X Selective reduction activity tends to increase.
[0026] The exhaust gas treatment catalyst of the present invention is NO X and SO X Exhaust gas containing NO, especially from boilers or waste incinerators, X Ya SO X NO is produced by catalytic reduction of exhaust gas containing heavy metals and dust by adding a reducing agent such as ammonia. X Removal and SO X It is suitably used in removal methods. Furthermore, the operating conditions for the exhaust gas treatment catalyst are the same as those for normal exhaust gas treatment, specifically, it can be used at a reaction temperature of 150°C to 400°C. In particular, the exhaust gas treatment catalyst of the present invention shows high activity in the temperature range of 170°C to 270°C, and especially in the temperature range of 170°C to 200°C, it produces good NO X Selective reduction activity and SO X It shows resistance.
[0027] <Method for manufacturing the exhaust gas treatment catalyst of the present invention> The method for producing the exhaust gas treatment catalyst of the present invention is described below. The exhaust gas treatment catalyst of the present invention can be prepared, for example, by a manufacturing method comprising the following steps. 1) A step of preparing a mother liquor by kneading water, sulfuric acid, vanadium raw material, molybdenum raw material, and complexing agent. 2) A step of preparing a compound by kneading titanium oxide powder and the mother liquor, and then kneading a precipitating agent into the compound to obtain a molding compound in which a coprecipitate of vanadium and molybdenum is fixed to the surface of the titanium oxide powder, and which further contains a silane coupling agent and latex. 3) A step of molding the molding paste to obtain a molded body. 4) A step of firing the molded body to obtain an exhaust gas treatment catalyst in which a composite oxide of vanadium and molybdenum is fixed to the surface of the titanium oxide powder.
[0028] The following details each step. <Steps for preparing the mother liquor> In the process of preparing the mother liquor, vanadium raw materials, molybdenum raw materials, a complexing agent, and sulfuric acid are dissolved in water to prepare the mother liquor. Here, vanadium and molybdenum serve as raw materials for forming the complex oxide. The complexing agent coordinates with vanadium or molybdenum ions to form a complex. By dissolving these raw materials in water, the mother liquor can be prepared.
[0029] For the vanadium and molybdenum raw materials, it is preferable to use soluble salts. For example, vanadate salts, vanadium sulfate, or vanadium chloride are preferred as vanadium raw materials, and ammonium metavanadate is particularly preferred. Vanadium oxide may also be dissolved in acid. As the molybdenum raw material, it is preferable to use molybdate salts, molybdenum sulfate, or molybdenum chloride, and it is particularly preferable to use ammonium molybdate. Alternatively, molybdenum oxide may be dissolved in acid. Furthermore, these may be used individually or in combination of two or more types. Furthermore, the amounts of vanadium and molybdenum added as raw materials are adjusted as appropriate to match the final composition of the exhaust gas treatment catalyst.
[0030] The complexing agent is preferably a compound having an amine and a hydroxyl group, more preferably an alkanolamine, and particularly preferably ethanolamine. These complexing agents coordinate with vanadium ions or molybdenum ions in the mother liquor to form a complex and stabilize it. Therefore, it is preferable to add the complexing agent after dissolving the vanadium and molybdenum raw materials in water.
[0031] In this case, the amount of complexing agent added is preferably in the range of 0.1 moles to 6 moles, and more preferably in the range of 0.5 moles to 3 moles, per mole of vanadium and molybdenum. By adding the amount of complexing agent necessary to form the complex in this way, the vanadium and molybdenum ions are stabilized.
[0032] The amount of sulfuric acid added is preferably in the range of 0.001 moles to 0.1 moles per mole of titanium, and more preferably in the range of 0.01 moles to 0.05 moles.
[0033] In the process of preparing this mother liquor, other soluble components may be added. For example, a raw material containing the aforementioned co-catalyst component may be dissolved.
[0034] <Process for obtaining a molded compound> In this step, the mother liquor prepared in the aforementioned step for preparing the mother liquor is kneaded with titanium oxide powder to prepare a kneaded product. It is preferable that the titanium oxide powder is surface-modified beforehand with an acid. The surface modifier (acid) used here can be either an inorganic acid or an organic acid, such as citric acid, acetic acid, nitric acid, phosphoric acid, or sulfuric acid.
[0035] Titanium oxide powder has a specific surface area of 250-500 m². 2 It is preferable that it be in the form of / g.
[0036] The compound contains latex. Preferably, the latex is an acrylate-based latex. This is because vanadium and molybdenum can be fixed to the titanium in a suitable oxide state in a highly dispersed manner, thereby improving catalytic performance. The latex content in the kneaded mixture is preferably 0.02 to 5.0% by mass. More preferably 0.05 to 1.0% by mass.
[0037] The kneaded mixture contains a silane coupling agent. Preferably, the silane coupling agent is one having an ethylene skeleton (a C=C double bond). The content of the silane coupling agent in the kneaded product is preferably 0.5% by mass or more and 10.0% by mass or less.
[0038] The kneaded material may further contain additives such as reinforcing materials and plasticizers that may also be included in the exhaust gas treatment catalyst of the present invention. Specifically, it is preferable to include inorganic components such as glass fibers, silica, and alumina. Including inorganic components tends to improve the moldability and strength of the exhaust gas treatment catalyst. When reinforcing agents and plasticizers are used as additives, the total content of reinforcing agents and plasticizers in the compound is preferably 5 to 30% by mass. More preferably, it is 5 to 15% by mass.
[0039] Conventional methods can be used for mixing. For example, a kneader, a high-speed mixer, or a ball mill can be used. These methods are appropriately selected depending on the amounts of mother liquor and titanium oxide powder. If the mixture becomes clay-like and puts a load on the equipment, it is preferable to use a kneader or a high-speed mixer.
[0040] Subsequently, the mixture and the precipitating agent are kneaded together to prepare a moldable mixture in which a coprecipitate of vanadium and molybdenum is fixed to the surface of the titanium oxide. Here, the mother liquor components contained in the mixture are neutralized, and a coprecipitate of vanadium and molybdenum is formed. This coprecipitate is fixed to the surface of the titanium oxide powder to obtain a moldable mixture.
[0041] Conventional precipitating agents can be used. For example, precipitating agents such as sodium carbonate, soda ash, and aqueous ammonia can be used. The amount of precipitating agent added is adjusted as appropriate so that the pH of the mother liquor contained in the kneaded mixture is in the range of 6 to 9. If the kneaded mixture is clay-like and it is difficult to measure the pH, the amount of precipitating agent needed to neutralize the mother liquor should be determined experimentally beforehand, and the amount added should be adjusted accordingly. If the kneaded mixture is not clay-like, the moisture content should be adjusted, a binder should be added, etc., to make it suitable for molding.
[0042] <Process for obtaining a molded body> In the process of obtaining a molded body, the molded compound is molded to prepare the molded body. It can be molded into conventionally known shapes such as pellets or honeycomb. For applications as an exhaust gas treatment catalyst, it is preferable to mold it into a honeycomb shape. Regarding the molding method, conventionally known methods can be used; for example, the material can be molded into pellets or honeycomb structures using an extrusion molding machine. The molded body should be dried using conventionally known methods to prevent cracking or other damage. The aforementioned exhaust gas treatment catalyst of the present invention may contain additives such as reinforcing materials and plasticizers, which may be included in the molded body, by molding them together with the kneaded material for the molded body.
[0043] <Process for obtaining an exhaust gas treatment catalyst> In the process of obtaining the exhaust gas treatment catalyst, the molded body is calcined to prepare an exhaust gas treatment catalyst in which a composite oxide of vanadium and molybdenum is fixed to the surface of a titanium oxide. Conventional known calcination methods can be used. For example, calcination in the atmosphere using a heating furnace such as an electric furnace or a gas furnace can be used. The calcination temperature is preferably between 300°C and 500°C. The calcination time depends on the calcination temperature, but is generally within the range of 1 hour to 48 hours. [Examples]
[0044] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited in any way to the examples provided.
[0045] [Measurement method] The measurement methods adopted in this application are described below.
[0046] [1] Composition The exhaust gas treatment catalysts obtained in the examples and comparative examples were powdered to prepare evaluation samples. A solution was prepared by dissolving this in acid, and the composition of various components was calculated using inductively coupled plasma emission spectroscopy (instrument name: ICPS-8100).
[0047] [2] Valence of vanadium and molybdenum Evaluation samples were prepared by fragmenting the reaction surfaces (outer surface for pellets, outer surface of the partitions for honeycomb structures) of the exhaust gas treatment catalysts obtained in the examples and comparative examples, so that these surfaces could be measured. These samples were placed on a sample stage and X-ray photoelectron spectroscopy (XPS) was performed under the following conditions. By analyzing the spectra obtained from these measurements, it was determined that the catalysts contained vanadium and molybdenum of these valencies if peaks were detected within the following ranges. <Measurement conditions> XPS measurements were performed using a ThermoFisher ESCALAB220IXL, with Al as the X-ray source. The peak position was corrected to a reference value of 284.8 eV for the CC coupling of C1S. After setting the evaluation sample in the instrument and confirming that high vacuum had been achieved, measurements were taken under the conditions of an acceleration voltage of 10 kV, an emission current of 10 mA, and 30 scans. <Calculation conditions> After scan integration, peak separation is performed using the built-in analysis software AVANTAGE, V 3+ , V 4+ , V 5+ Mo 6+ Check for the presence or absence of a peak.
[0048] [3] NMR spectrum The exhaust gas treatment catalysts obtained in the examples and comparative examples were powdered for measurement and uniformly packed into a 5.0 mm diameter solid NMR sample tube to prepare evaluation samples. These were then placed on a sample stage and Si-NMR measurements were performed under the following measurement conditions. By analyzing the spectra obtained from these measurements, if a peak was detected at the following chemical shift values (horizontal axis), it was determined that Si was present in the catalyst in the forms shown below (Q1~Q4). Q1: -81ppm Q2: -90ppm Q3: -101ppm Q4: -110 ppm
[0049] [ka]
[0050] <Measurement conditions> Si-NMR measurements of the sample surface were performed using an Agilent NMR-600 spectrometer under the following measurement conditions. 1 H resonance frequency: 600MHz 29 Si resonance frequency: 119.2MHz Magic angle: 54.7° Rotation speed: 6kHz Measurement method: Single pulse method Pulse flip angle: 90° Pulse repetition time: 400 seconds Objective lens magnification: 100x Secondary standard material: PDMS (polydimethylsilane) PDMS detection peak: -34.44 ppm <Calculation conditions> After measurement, peak separation was performed using the analysis software "Origin" to separate the peaks, and the following intensity ratios were determined using the peak areas S of the peaks corresponding to Q1 to Q4. (Q1+Q2) / (Q3+Q4)=(S Q1 / +S Q2 ) / (S Q3 +S Q4 )
[0051] [4] Strength After cutting out 75mm x 75mm cubes from the catalysts obtained in Examples 1-2 and Comparative Examples 1-2, they were compressed perpendicular to the direction of penetration of the honeycomb through-holes, and the pressure at which the catalyst was completely destroyed was measured. The results are shown in Table 1. The unit of pressure values in Table 1 is Pa.
[0052] [5] Specific surface area (SA) Titanium oxide used as a raw material in the examples and comparative examples was pulverized to prepare an evaluation sample. This evaluation sample (0.2 g) was placed in a measuring cell and degassed at 300°C for 60 minutes in a nitrogen gas stream. Then, the sample was maintained at liquid nitrogen temperature in a mixed gas stream of 30% nitrogen and 70% helium by volume, allowing nitrogen to be adsorbed to equilibrium on the sample. Next, the temperature of the sample was gradually raised to room temperature while flowing the mixed gas, and the amount of nitrogen desorbed during this time was detected. The specific surface area of the sample was then measured using a pre-prepared calibration curve.
[0053] [6] Denitrification performance (selective reduction catalyst (SCR) activity) The exhaust gas treatment catalysts obtained in the examples and comparative examples were cut into the following catalyst shapes to prepare evaluation samples. These were packed into a flow-through reactor, and the denitrification rate was evaluated. Specifically, NO before and after catalyst contact was measured under the following conditions. X The denitrification rate was calculated from the concentration using the following formula. The denitrification rate was defined as the "initial denitrification rate" immediately after circulating gas composition 1 for 3 hours, and then as the "denitrification rate after degradation test" immediately after circulating gas composition 2 at a reaction temperature of 175°C for 100 hours. In Table 1, the "initial denitrification rate" when the reaction temperature is 175°C is labeled as "Denitrification performance (175°C)", and the "initial denitrification rate" when the reaction temperature is 300°C is labeled as "Denitrification performance (300°C)". In Table 1, the "denitrification rate after degradation test" is labeled as "Denitrification performance after accelerated degradation test (175°C)". Note that nitrogen oxides (NO) in the gas before and after contact with the catalyst X The concentration was measured using a chemiluminescent nitrogen oxide analyzer (ECL-88AO, manufactured by Anatech Yanaco Co., Ltd.). Denitrification rate (%) = [NOx in gas before contact] X (ppm) - NO in gas after contact X (ppm)] / NOx in gas before contact X (ppm) × 100 <Test Conditions> • Catalyst shape: 4x4 mesh, length 286mm Reaction temperatures: 175°C, 300°C • Reaction time: 100 hours ·SV:18528.39h-1 • Gas composition 1: NO X =200ppm, NH3=200ppm, O2=5%, H2O=10%, N2=balance • Gas composition 2: NO X =200ppm, NH3=200ppm, O2=5%, H2O=10%, SO2=80ppm, N2=balance
[0054] [Example 1] <Steps for preparing mother liquor 1> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78%) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5%) was added, followed by stirring for 5 minutes. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 1 containing vanadium and molybdenum.
[0055] <Steps to obtain molding compound 1> 20766g of titanium dioxide (Tronox: G5: TiO2 oxide concentration 82%), 2272g of anhydrous citric acid (Fuso Chemical Co., Ltd.), and 2000g of water were kneaded in a kneader for 10 minutes. Then, the aforementioned mother liquor 1 was added and kneaded for 30 minutes. After that, 703g of carboxymethylcellulose (Nichirin Chemical Co., Ltd.; ammonium CMC) was added and kneaded for 10 minutes. To the resulting mixture, 8276g of aqueous ammonia (concentration: 15% by mass) was added as a precipitating agent and kneaded for 30 minutes while heating to evaporate the water. Subsequently, 3000g of glass fiber (E-glass) and 300g of KBM5103, a silane coupling material manufactured by Shin-Etsu Silicone Co., Ltd., were added as structural restricting materials and kneaded for 10 minutes. Then, 4216g of Nipol LX874 (manufactured by Nippon Zeon Co., Ltd.), a 45% concentration acrylate latex, was diluted 25 times with water and added, and kneaded for 20 minutes to obtain molding compound 1.
[0056] <Steps to obtain exhaust gas treatment catalyst 1> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the moldable mixture 1 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends of the honeycomb through-holes in the central axis direction (longitudinal direction) were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 1 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.
[0057] Figure 1 shows the NMR spectrum of the exhaust gas treatment catalyst obtained in Example 1.
[0058] Figure 2 shows a scanning electron microscope (SEM) image of the exhaust gas treatment catalyst obtained in Example 1. Figure 2 is a 100x SEM image. From this image, it appears that the adhesion between the glass fibers and the catalyst components is high, and there are few spaces created by the aggregation of glass fibers.
[0059] [Example 2] <Steps to prepare mother liquor 2> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78%) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5%) was added, followed by stirring for 5 minutes. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 2 containing vanadium and molybdenum.
[0060] <Steps to obtain molding compound 2> 20766g of titanium dioxide (Tronox: G5: TiO2 oxide concentration 82%), 2272g of anhydrous citric acid (Fuso Chemical Co., Ltd.), and 2000g of water were kneaded in a kneader for 10 minutes. Then, the aforementioned mother liquor 2 was added and kneaded for 30 minutes. After that, 703g of carboxymethylcellulose (Nichirin Chemical Co., Ltd.; ammonium CMC) was added and kneaded for 10 minutes. To the resulting mixture, 8276g of aqueous ammonia (concentration: 15% by mass) was added as a precipitating agent and kneaded for 30 minutes while heating to evaporate the water. Subsequently, 3000g of glass fiber (E-glass) and 300g of KBE1003, a silane coupling material manufactured by Shin-Etsu Silicone Co., Ltd., were added as structural restricting materials and kneaded for 10 minutes. Then, 4216g of Nipol LX874 (manufactured by Nippon Zeon Co., Ltd.), a 45% concentration acrylate latex, was diluted 25 times with water and added, and kneaded for 20 minutes to obtain molding compound 2.
[0061] <Steps to obtain exhaust gas treatment catalyst 2> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the molded mixture 2 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 2 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.
[0062] [Comparative Example 1] <Steps to prepare mother liquor 3> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78%) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5%) was added, followed by stirring for 5 minutes. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 3 containing vanadium and molybdenum.
[0063] <Steps to obtain molding compound 3> 20766g of titanium dioxide (Tronox: G5; TiO2 oxide concentration 82%), 2272g of anhydrous citric acid (Fuso Chemical Co., Ltd.), and 2000g of water were kneaded in a kneader for 10 minutes. Then, the aforementioned mother liquor 3 was added and kneaded for 30 minutes. Next, 703g of carboxymethylcellulose (Nichirin Chemical Co., Ltd.; ammonium CMC) was added and kneaded for 10 minutes. To the resulting mixture, 8276g of aqueous ammonia (concentration: 15% by mass) was added as a precipitating agent and kneaded for 30 minutes while heating to evaporate the water. Then, 3000g of glass fiber and 300g of KBM5103 (Shin-Etsu Silicone Co., Ltd.), a silane coupling material, were added as structural restricting materials and kneaded for 10 minutes to obtain molding mixture 3.
[0064] <Steps to obtain exhaust gas treatment catalyst 3> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the moldable mixture 3 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 3 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.
[0065] [Comparative Example 2] <Steps to prepare mother liquor 4> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78%) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5%) was added. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 4 containing vanadium and molybdenum.
[0066] <Step to obtain molding compound 4> 20766g of titanium dioxide (Tronox: G5: TiO2 oxide concentration 82%), 2272g of anhydrous citric acid (Fuso Chemical Co., Ltd.), and 2000g of water were kneaded in a kneader for 10 minutes. Then, the aforementioned mother liquor 4 was added and kneaded for 30 minutes. After that, 703g of carboxymethylcellulose (Nichirin Chemical Co., Ltd.; ammonium CMC) was added and kneaded for 10 minutes. 8276g of aqueous ammonia (concentration: 15% by mass) was added to the resulting mixture as a precipitating agent and kneaded for 30 minutes while heating to evaporate the water. Then, 3000g of glass fiber (E glass) was added as a structural restricting agent and kneaded for 10 minutes. Finally, 4216g of Nipol LX874 (Nippon Zeon Co., Ltd.), a 45% concentration acrylate latex, diluted 25 times with water, was added and kneaded for 20 minutes to obtain molding mixture 4.
[0067] <Steps to obtain molded body 4> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the molded mixture 4 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 4 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.
[0068] Figure 3 shows a scanning electron microscope (SEM) image of the exhaust gas treatment catalyst obtained in Comparative Example 2. Figure 3 is a 100x SEM image. From this image, it can be seen that the adhesion with the catalyst component is weak, and spaces are created in the catalyst structure due to the aggregation of glass fibers. Comparing Figure 3, which shows the case of the comparative example, with Figure 2, which shows the case of the example, it appears that the adhesion between the glass fibers and the catalyst component is higher in Figure 2 of the example than in Figure 3 of the comparative example, and that there are fewer spaces created by the aggregation of glass fibers. As a result, the honeycomb structure in Figure 2 has high adhesion of the catalyst component including glass fibers and maintains its strength (N / cm²) even in the honeycomb structure. 2 I believe that ) is strong.
[0069] [Comparative Example 3] <Steps to prepare mother liquor 5> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78%) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5%) was added. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 5 containing vanadium and molybdenum.
[0070] <Steps to obtain molding compound 5> 20766g of titanium dioxide (Tronox: G5; TiO2 oxide concentration 82%), 2272g of anhydrous citric acid (Fuso Chemical Co., Ltd.), and 2000g of water were kneaded in a kneader for 10 minutes. Then, the aforementioned mother liquor 5 was added and kneaded for 30 minutes. After that, 703g of carboxymethylcellulose (Nichirin Chemical Co., Ltd.; ammonium CMC) was added and kneaded for 10 minutes. 8276g of aqueous ammonia (concentration: 15% by mass) was added to the resulting mixture as a precipitating agent and kneaded for 30 minutes while heating to evaporate the water. Then, 3000g of glass fiber (E glass) was added as a structural restricting material and kneaded for 10 minutes to obtain molding mixture 5.
[0071] <Steps to obtain molded body 5> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the molded mixture 5 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 5 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.
[0072] [Comparative Example 4] <Steps to prepare mother liquor 6> 3000g of water, 330g of monoethanolamine as a complexing agent, and 691.3g of ammonium metavanadate were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C to prepare mother liquor 6.
[0073] <Steps to obtain the moldable kneaded body 6> 18,330 g of titanium dioxide (manufactured by Ishihara Sangyo Co., Ltd.: MC90: TiO2 oxide concentration 95%), 1,411.99 g of ammonium metavanadate, 809.82 g of ammonium molybdate, and aqueous ammonia (concentration: 15% by mass) were kneaded in a kneader for 30 minutes. Then, the mother liquor 6 prepared in the above step was added and kneaded for 30 minutes. Furthermore, 1,710 g of glass fiber was added as a structural restricting agent and kneaded for 10 minutes. Finally, 300 g of an organic binder, which serves as a molding aid, was added and kneaded for 20 minutes to obtain the moldable mixture 6.
[0074] <Steps to obtain molded body 6> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the molded mixture 6 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 1 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.
[0075] [Table 1]
Claims
1. A composite oxide containing vanadium and molybdenum is fixed to the surface of a titanium oxide, An exhaust gas treatment catalyst, in which peaks obtained by Si-NMR are separated into Q1 to Q4, and the peak area ratio of (Q1+Q2) / (Q3+Q4) is 4.5 or more.
2. The exhaust gas treatment catalyst as described in claim 1, characterized in that the complex oxide containing vanadium and molybdenum is composed of a mixed valence compound containing trivalent, tetravalent and pentavalent vanadium and hexavalent molybdenum.
3. The exhaust gas treatment catalyst according to claim 1, characterized in that it contains 0.1 to 5 mass % of sulfur calculated as SO 4 .
4. A process for producing a mother liquor by dissolving sulfuric acid, a vanadium raw material, a molybdenum raw material, and a complexing agent in water; kneading the mother liquor with titanium oxide powder to obtain a kneaded mixture; A step of kneading the kneaded product with a precipitating agent to obtain a kneaded body for molding; A molding step of molding the kneaded mixture to obtain a molded body; and calcining the molded body to obtain an exhaust gas treatment catalyst. The method for producing an exhaust gas treatment catalyst, wherein the molding kneaded body in the molding step contains a silane coupling agent and latex.